Etudiantes américaines, militantisme et guerre du Vietnam : guerre, paix et « genre » dans les années 1960 - Alexandra Boudet-Brugal (Amnis)
The opposition to the Vietnam War (1964 – 1973) was unprecedented in American history; and the universities took the center stage. As a sub-group, the female students deserve a particular attention. First because the interaction between sexuality/gender and war is part of History and any war story, and second, their increasing number from the mid 1950s on suggests that they made up a new and unexpected “force” that significantly added to the opposition. Thus, this paper explores what made up the female activist experience. I will then remark on the perception(s) of their roles that oscillated between tradition and change. This involves in turn an examination of the notions of legitimacy and visibility of female activism. Last, I will consider the consequences of the inconsistencies between the Movement ideals and rhetoric and the reality as far as gender roles were concerned. Ultimately, this paper will briefly assess if women’s roles and voices as activists in the public and political sphere have generated a new discourse.